Bioactivity Potential and Chemical Compounds of Cinnamomum: Literature Review - Putri Wulandari; Elsa Yuniarti (Postgraduate, University of Mataram, 2023)
Cinnamon is a spice commodity that contains chemical compounds and bioactive components that have the potential to be developed as medicinal raw materials in the pharmaceutical industry. Biological activity in cinnamon can increase and stimulate the body's immune system. This study aims to present a summary of the literature review to unify the overall information on bioactivity and chemical compound content in cinnamon. The research method uses the literature review method with the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) meta-analysis approach. The literature review of original research articles shows a variety of properties found in cinnamon plants because of alleged chemical compounds including cinnamaldehyde, phenolics, flavonoids, alkaloids, saponins, tannins, polyphenols, triterpenoids as potential bioactivities, namely immunomodulator, antifungal, antioxidant, anti-inflammatory, antibacterial, antidiabetic and A-Glucosidase enzyme activity. From some research results, cinnamon plant parts have been shown to have many pharmacological properties that it can increase the productivity of drugs using natural ingredients